Asthma prevalence in Norwegian Elite Athletes - Melsom, H. S.; Randa, A.; Stang, J.; Hisdal, J.; Stensrud, T. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Asthma is a common problem among elite athletes and represents a health risk interfering with the athlete`s performance status. This study aimed to evaluate the asthma prevalence in Norwegian summer and winter elite athletes and asthma prevalence across sport categories. We also aimed to examine if bronchial hyperresponsiveness (BHR), lung function, fraction of exhaled nitric oxide (FENO) and allergy differed between asthmatic and non-asthmatic elite athletes.